PENGEMBANGAN MODEL PEMBELAJARAN GERAK DASAR LARI MELALUI PERMAINAN THROW AND RUN PADA SISWA BERKEBUTUHAN KHUSUS (TUNARUNGU) DI SDLB NEGERI SEMARANG TAHUN 2015 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research it was produce a model of learning basic movement for kind of run by means thegame Throw and Run on students with special condition (physical defect) in Semarang State SDLB2015.There was product to development procedure includes product analysis to would be created, develop earlyactivities, expert validation and revision, testing and revision of the small group, large group and test the finalproductTest result experts data obtained by the average percentage of the results analysis of the product was76.66% of "good" criteria, therefore it could be used. Data observations and student questionnaire on a smallscale trial gained an average of the percentage was 75.05% of "good". Data observations and studentquestionnaires large scale trial gained an average of the percentage was 79.25% of "good". The data on testingsmall group and large trial group to proof observation increase and questionnaires students in percentage of4.2%.Based on results this research, the conclusion that the basic learning run model through the game Throwand Run could be used for every students with hearing impairment in SDLB Semarang.